Dari Nilai Budaya Lokal ke Ruang Kelas: Tinjauan Sistematis tentang Nilai Budaya Lokal yang Dimanfaatkan dalam Pembelajaran Berbasis Etnosains - Ratih, Arista; Ekawati, Darmanella Dian; Festiyed, Festiyed; Asrizal, Asrizal; Diliarosta, Skunda; Desnita, Desnita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to provide a comprehensive picture of the current state of ethnoscience integration in science learning and analyze the impact of this integration on students' understanding and appreciation of science, and explore the challenges and opportunities presented by this approach. This article was prepared based on the results of a systematic review of 16 articles published in 6 SCOPUS indexed journals and 10 SINTA accredited journals from 2020-2023. The results of the research show, 4 articles highlight Sasak cultural values, Dayak cultural values, local values of ulos weaving, local wisdom of the Sorong West Papua community, Badui traditional cultural values, Laot customary law, Congklak traditional games, Bebentangan traditional games, Banjar traditional language, local wisdom of syafaral anam, and cultural values of the Bugis tribe. Keywords: Ethnoscience Integration, Local Cultural Values